Peter C. Peterson letter to Nicholas S. Halmi regarding bird sighitings, February 13, 1977 - Petersen, Peter C.et al (1977)
Letter from Peter C. Petersen to Nicholas S. Halmi, dated February 13, 1977, that details various bird sightings, including a Black-legged Kittiwake at the Duane Arnold Energy Center by Bryan Gielins on January 22 and 23, 1977. Epson - sheet feed